(3OjhGf CHj fhGSs - (3CHh fhGS , GdMSf Hf gGfjA Hf YHO GdGhd Hf UHGM GdMcej HGdhdGA, CHh fhGS,J (B198 (3g` s
(3BNQgG (B:s
(3JfJgi MQa GdbGa s
(3GdfSNI HgG MhGTs
(3QhGjI CHj HcQ GdUhdis
(3Ydjg JYdjbGJ cKjQI Ydi GdMGTjI hgj ZjQ cGedI hJfJgi HMQa GdbGas
(3fSNI KGfjI s
(3hQO CjVkG JMJ Qbe (B2181 , 2191 , 475 s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs